Projecting Economic Power in The Baltic Sea Region. Representations of Space and Power in the Cyber Security Strategies of Three European Union Member States in The Baltic Sea Region Between Early 2015 and Late 2016 - Huvinen, Juha (fi=Turun yliopisto|en=University of Turku|, 2018)
This thesis approaches cyber security in relation to power and space in three states around the Baltic Sea Region. Thesis is based on power theories of Michel Foucault. The key goal in the study is to find out how cyber security is being produced as political and spatial problem in the Estonian, Finnish and Danish cyber security strategies and selected context material. Theoretical background of the thesis is based on work of Michel Foucault and Thomas Nail. Most important part of the theoretical frame is the genealogy of power. The spatial dimension is based on the idea of cyberspace. Cyberspace is approached through anthropological and geographical research. The most important term in this case is the concept of liminal. The concept of liminal is based on the theory regarding rites of passage by Arnold Van Gennep. Second important theoretical approach comes from anthropologist Mary Douglas. The anomaly is second key term that can be attached to properties of cyberspace. The main material consists of three national cyber security strategy papers from Finland, Denmark and Estonia. There is also some context material to support the analysis. This support material includes government resolutions, strategy papers and risk assessments. Research material has been mostly active in research period from early 2015 to late 2016. The research method that is used in this thesis is What the Problem Represents to be Analysis by Carol Bacchi. Analysis is based on the idea that we are governed through problematizations. The analysis of the material clearly indicates that there are similar themes and features in all three cyber security strategies. Key features and themes include: securing the national infrastructure, cyber security as a tool for competitive advantage, more efficient authorities, more international cooperation, and more cooperation between public and private sectors. These goals are going to be met in cyber environment that is complex and changes fast. There are risks that are produced by skillful hackers and foreign governments. Analysis indicates that most of the measures mentioned in cyber security strategies are on national level. Cyberspace is seen as liminal, borderless and partly chaotic. This space produces both threats and benefits. Cyber security strategies and reports can be seen as one more link towards containment of risks rising from liminal cyberspace. Power relations between different private and public sector actors are complex. There is no direct link between individual citizen and the sovereign power. The sovereign projects power mainly through strategic delegation of tasks and resources.

Tutkielma lähestyy kyberturvallisuuden kytkeytymistä valtaan ja tilaan kolmessa Itämeren rantavaltiossa perustuen Michel Foucault'n vallan luonnetta sivuavaan tutkimukseen. Tutkimuksen keskeisenä tavoitteena on selvittää kuinka kyberturvallisuutta tuotetaan sekä poliittiseen valtaan liittyvänä että tilallisena ongelmana Suomen, Viron ja Tanskan kyberturvallisuusstrategioissa ja niihin välittömästi kytkeytyvässä oheismateriaalissa. Tutkielman teoreettinen tausta rakentuu nojautuen Michel Foucault'n vallan genealogiaan ja Thomas Nailin tulkintaan valtasuhteiden epävakaasta luonteesta. Työn spatiaalinen ulottuvuus rakentuu sekä maantieteen että kulttuuriantropologian kautta muodostettuun kuvaan kybertilasta. Tässä keskeistä on liminaalin käsite, joka perustuu erityisesti Arnold Van Gennepin teoriaan siirtymäriiteistä. Myös antropologi Mary Douglasin tulkinnalla anomaliasta on tärkeä rooli kybertilan jäsentämisessä. Työn aineistona on käytetty kansallisia kyberturvallisuusstrategioita Suomesta, Tanskasta ja Virosta. Analyysiä tukemassa hyödynnetään myös muuta kyberturvallisuutta sivuavaa kontekstimateriaalia, kuten hallituksen päätöslauselmia, strategioita ja riskianalyysejä. Tutkimusmateriaali on ollut voimassa tarkasteluajankohtana vuosien 2015–2016 välillä. Työn metodisena ratkaisuna hyödynnetään soveltaen Carol Bacchin kehittämää What's the Problem Represents to Be-analyysiä. Analyysi perustuu keskeisiltä osin ajatukseen, jonka mukaan ongelmat ja niiden muotoilu ovat keskeinen osa hallintoa. Analyysin tulokset osoittavat, että kyberturvallisuus ja siihen kytkeytyvä vallankäyttö sisältävät strategioissa toistuvia elementtejä. Strategioiden keskeisenä tavoitteita ovat infrastruktuurin ja keskeisten järjestelmien suojaaminen, kansallisen kilpailukyvyn parantaminen kyberturvallisuuden kautta, tehokkaamman viranomaistoiminnan takaaminen, kansainvälinen yhteistyö sekä yksityisen ja julkisen sektorin yhteistyö. Näihin tavoitteisiin pyritään toimintaympäristössä, joka kuvataan nopeasti muuttuvana, monimutkaisena ja alttiina yhtä taitavampien hakkerien ja valtiollisten toimijoiden toimille. Analyysi osoittaa myös, että kyberturvallisuusraporttien ehdottamat toimet ovat spatiaalisesti liittyneet ensisijaisesti kansallisvaltioon, jolle liminaalinen, ylirajainen ja osin kaoottinen kybertila luo sekä uhkia että mahdollisuuksia. Kyberturvallisuusstrategiat ja raportit ovat osa pyrkimystä hillitä internetin liminaalista luonteesta nousevaa uhkaa. Kyberturvallisuuteen liittyvien toimijoiden väliset valtasuhteet ovat monimutkaisia ja strategioiden suhde yksittäiseen kansalaiseen on välillinen. Suvereenin vallankäyttö perustuu vallan delegointiin toisille toimijoille.